2015
DOI: 10.1016/j.cortex.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Phonological short-term memory in logopenic variant primary progressive aphasia and mild Alzheimer's disease

Abstract: It has been argued that individuals with logopenic variant primary progressive aphasia (lvPPA) have an impairment of the phonological loop, which is a component of the short-term memory (STM) system. In contrast, this type of impairment is not thought to be present in mild typical Alzheimer’s disease (AD). Thus, one would predict that people with lvPPA would score significantly lower than a matched AD group on tasks that require phonological STM. In the current study, an lvPPA group was compared with a mild AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 52 publications
2
32
0
8
Order By: Relevance
“…The findings suggest that common language and working memory deficits occur in lvPPA and multi‐domain AD. Our findings differ from those of some previous studies, which have found differences between AD and lvPPA patients in the realm of verbal working memory (Foxe et al ., ; Meyer et al ., ) and language (Ahmed et al ., ). Differences in findings might reflect phenotypic variation in study cohorts, of which age is known to be one determinant (Snowden et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The findings suggest that common language and working memory deficits occur in lvPPA and multi‐domain AD. Our findings differ from those of some previous studies, which have found differences between AD and lvPPA patients in the realm of verbal working memory (Foxe et al ., ; Meyer et al ., ) and language (Ahmed et al ., ). Differences in findings might reflect phenotypic variation in study cohorts, of which age is known to be one determinant (Snowden et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In lvPPA, disease in the left inferior parietal lobule and superior and middle temporal gyri disturbs the phonological loop of verbal working memory (phonological short-term memory or store that holds phonological traces for brief periods) 68,83 , resulting in deficits in digit, letter, and word span and an absent phonological similarity effect 84 .…”
Section: Introductionmentioning
confidence: 99%
“…During these sessions, participants completed a battery of language and cognitive tests, including the Montreal Cognitive Assessment (MoCA; Nasreddine et al, 2005), the BNT, the 3-Picture version of the Pyramids and Palm Trees test (P&PT; Howard & Patterson, 1992), Word-Picture Matching (Rogers & Friedman, 2008), subject and object Wh-questions from the Northwestern Anagram Test (NAT; Weintraub et al, 2008), selected subtests from the Boston Diagnostic Aphasia Examination (BDAE; Goodglass et al, 2001), repetition of 5-syllable pseudowords (Meyer, Snider, Campbell, & Friedman, 2015), and the reading of irregular and regular words. The reading task was developed at the Center for Aphasia Research and Rehabilitation at Georgetown University Medical Center.…”
Section: Methodsmentioning
confidence: 99%
“…All of these studies have found positive treatment effects in lvPPA. Treatment types have included combined phonological/orthographic (Croot et al, 2015; Newhart et al, 2009), semantic/orthographic (Beeson et al, 2011), and semantic/phonological/orthographic (Beales et al, 2016; Henry et al, 2013) interventions, while Meyer et al (2015) utilized separate phonological and orthographic treatments. Four of these studies found item generalization (Beales et al, 2016; Beeson et al, 2011; Henry, et al, 2013; Newhart et al, 2009), while Meyer et al (2015) found cross-language transfer within confrontation naming and naming to definition tasks.…”
Section: Introductionmentioning
confidence: 99%